EMPOWERING SEBANI’S STREET CHILDREN THROUGH HIJAIYAH LITERACY AND PRAYER:: A Step Toward Religious Life - Dewi, Dewi Masita; M. Mahbubi (BAMALA Institute, 2025)
Community Service Activity (PKM) with the title